Unilateral Giant Varicocele Mimicking Inguinal Hernia Resulting from Portosystemic Shunt without Evidence of Portal Hypertension: An Unusual Case Report - Muhammed Zahir; Hassan R. Al Muttairi; Surjya Prasad Upadhyay; Piyush N. Mallick (Case Reports in Surgery)
Isolated giant varicocele has been reported with portal hypertension that results in abnormal communication between portal venous system and testicular vein venous system resulting in retrograde backflow of blood into the testicular venous system which leads to varicosity of the pampiniform plexuses. 65-year-old male with no past medical or surgical history presented to us with soft inguinoscrotal swelling that disappears on lying down mimicking inguinal hernia. Clinical examination revealed soft inguionoscrotal swelling that disappears on pressure. Ultrasonography revealed varicosity of pampiniform plexus, and CT angiography to trace the extent of the varicosity revealed abnormal communication of right testicular vein with superior mesenteric vein. There was no evidence of any portal hypertension; the cause of the portosystemic shunt remains obscure, and it might be a salvage pathway for increasing portal pressure. The case is noteworthy for its rare presentation and abnormal communication with portal venous system in the absence of evidence of portal hypertension.